Crisis of the 9th Generation Game Consoles-Focus on Playstation 5 and Xbox Series X - Szabados, György Norbert; Bácsné Bába, Éva; Fenyves, Veronika; Bács, Zoltán; Pfau, Christa; Szabados, Krisztián; Ráthonyi, Gergely (International Journal of Engineering and Management Sciences, 2021)
By the end of the past centrury, specific computers optimized for gaming, that is meeting the needs of the computer gamers, the so-called game consoles were introduced to the market. At the end of the last year, after waiting for so long, new types of the 9th generation consoles came into the market, produced by the Microsoft and the Sony. Ovation of this appearance is familiar and usual in the profession, which soon became exchanged by the space of dissatisfaction, since now, after  the events of the past months we can declare that gaming on both platforms suffers from serious difficulties. This study, the methodological base of which is composed by case study, secondary analysis of available data, intends to highlight the facts which led to this situation, whether it is a temporary or a permanent situation, and  how the market and the gaming society react to it. Results show that it does not seems to be a temporary phenomenon, and as a result of complex problems market anomalies have appeared, which considerably influences our relationship to the market of the consoles.